EFEKTIVITAS MODEL PEMBELAJARAN PREDICT, OBSERVE, EXPLAIN (POE) PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMP NEGERI SELANGIT - Dina Mitasari; Idul Adha; Nur Fitriyana (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the effectiveness of the Predict, Observe, Explain (POE) learning model in mathematics learning for VII grade students of SMP Negeri Selangit. This research is in the form of quasi-experimental. The population is all grade VII students of SMP Negeri Selangit in the academic year 2019/2020, totaling 98 students and as a sample are class VII.3 students, amounting to 24 students. Data collection is done by test and non-test techniques. The collected data were analyzed using t-test at a significant level α = 0.05. Based on the results of the study showed the effectiveness of the Predict, Observe, Explain (POE) learning model in mathematics learning with an average score of 74.44 with the percentage of students completing 79.17% of students' responses to learning in the good category with a percentage of 72.44 %, and student learning activities in the quite active category with a percentage of 28.45%.